ICHHAFTIGKEIT DALAM PERSPEKTIF ISLAM - Muhammad Bashori Muchsin (Turatsuna : Jurnal Keislaman dan Pendidikan, 2019)
Ichhaftigkeit is a term that represents selfishness and individualism. A person who prioritizes his own interests or places the interests of others not as his interests, can be classified as a group of human that justifies ichhaftigkeit. Human who puts themselves in this way are clearly contrary to the doctrine of Islam, because in Islamic teachings, each individual can be called as a useful human figure if his presence provides benefits to the others’ life. Such life is one of indicators that Islam is rahmatan lil-alamin. Keywords: Islam, self-interest, useful life Ichhaftigkeit merupakan istilah yang mewakili egoisme dan individualisme. Seseorang yang mengutamakan kepentingannya sendiri atau menempatkan kepentingan sesama bukan sebagai kepentinan dirinya, dapat digolongkan sebagai golongan manusia yang membenarkan ichhaftigkeit. Manusia yang menempatkan dirinya demikian ini jelas berlawanan dengan doktrin Islam, karena dalam ajaran Islam, setiap individu dapat disebut sebagai sosok manusia bermanfaat jika kehadirannya memberikan manfaat bagi kehidupan sesamanya. Hidup demikian menjadi salah satu indikator, bahwa Islam iu rahmatan lilalamin. Kata Kunci: Islam, kepentingan sendiri, hidup bermanfaat